2018
DOI: 10.2147/dmso.s166875
|View full text |Cite
|
Sign up to set email alerts
|

Relative handgrip strength as a marker of metabolic syndrome: the Korea National Health and Nutrition Examination Survey (KNHANES) VI (2014–2015)

Abstract: PurposeMuscles play an important role in energy metabolism. Several studies have investigated the association between muscle mass and metabolic syndrome (MetS), reporting conflicting results. However, studies concerning the association between muscle strength and MetS are limited. We aimed to investigate the association between relative handgrip strength (HGS) and MetS in Korean adults.Participants and methodsWe analyzed data from 5,014 Korean adults aged ≥20 years (2,472 men and 2,542 women) who participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 44 publications
(55 reference statements)
6
61
0
2
Order By: Relevance
“…In recent studies, relative HGS, adjusted for BMI, was inversely related to cardiometabolic risk. 12,15,22) The results of our study are consistent with this previous research. On the other hand, the relationship between absolute muscle strength and dyslipidemia remains controversial.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In recent studies, relative HGS, adjusted for BMI, was inversely related to cardiometabolic risk. 12,15,22) The results of our study are consistent with this previous research. On the other hand, the relationship between absolute muscle strength and dyslipidemia remains controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Relative to absolute HGS, relative HGS has stronger associations with metabolic syndrome and its component parameters, including high-density lipoprotein cholesterol (HDLC), TG, fasting glucose, and BP. 12) In addition, previous reports have shown that relative HGS is negatively associated with cardiometabolic risk 14,15) and predicts cardiovascular and all-cause mortality among middle-aged and elderly people. 16) This study aimed to evaluate the association between relative HGS and dyslipidemia, and to investigate the hypothesis that low relative HGS is associated with dyslipidemia.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A measure of three times was reported as an average. RHGS was estimated as the average value for maximum grip strength of the dominant hand divided by BMI, as previously reported (10)(11)(12)(13).…”
Section: Hand-grip Strengthmentioning
confidence: 99%
“…Many recent studies have established that low HGS is connected with different health outcomes including metabolic and cardiovascular risk factors. However, rather than absolute HGS, relative HGS (RHGS) adjusted for body mass index (BMI) has been proposed as an easy instrument for assessing metabolic health and cardiovascular risk in public health and clinical practice (10)(11)(12)(13).…”
Section: Main Text Introductionmentioning
confidence: 99%